The impact of domestic violence on the deviant behavior of high Junior stage students - Altaniji, Baina; Barhomi, Wafa (Al-Adab Journal, 2023)
Like the family, the basic cell in building the human society and the basic structure of the class is the behavior and direction of the individual. Perhaps the main reason that makes it so important and entrusts it with this great role is the multiplicity and different tasks and social and educational functions for which it is responsible and which it performs. The family is a social institution that exists in all human societies. Institutions and the most influential in groups as well as individuals, where individuals within the family learn the foundations and rules of behavior and the flow and mechanisms of interaction and dealing with others, and through the family begins the formation of the social psychology of the child, through the fusion and union that takes place between the child and his family, where the medical process of union these basic psychological needs and requirements For the child, such as love and tenderness, and the parents become a source of safety and stability for the child, who turns to them when feeling tense and fearful. The phenomenon of domestic violence is not a modern phenomenon within human societies, but rather it has existed for a long time. Despite the importance of this phenomenon in human societies and its appearance in different and varied forms and methods, studies that I meant this phenomenon and highlighted the dimensions Psychological and social has a bottle, and perhaps the main reason for its channel is the cases of secrecy and non-disclosure of domestic violence by family members for various reasons related to the customs and traditions of the prevailing societies and the fear of the surrounding view of them in addition to the misunderstanding of the teachings of religion in Islam, based on the foregoing sought through this research To study cases of domestic violence to which children are subjected to by their parents, whether verbally, morally or physically, and the extent of its impact on children’s deviant behaviors, whether through actions or behaviors, or through manifestations of disobedience to parents, among middle school students. In this study, we sought to clarify the concept of family fodder, especially violence directed towards children, and to identify the reasons behind it and the forms in which it appears, in addition to clarifying the effects resulting from family violence. The attitude of children and children, which appears clearly and clearly in their behavior and personalities, with mentioning the most prominent theories of negligence in the phenomenon of domestic violence.